PEMBINAAN NARAPIDANA MENURUT SISTEM PERMASYARAKATAN - Petrus Irwan Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2018)
With the application of the penal system, we leave the prison system. This change is not just a change of terms. The imprisonment system deals with acquaintance and imprisonment, its form is suffering and torture. In the penal system we are dealing with guidance and coaching. By preparing prisoners and students for social reinte- gration with their communities which is realized through the provision of guidance and coaching in the physical and spiritual elds. In the prison system the relationship between of cers and prisoners is a relationship between guard and guarded; whereas in a penal system the relationship is the relationship between the builder and the coached. In the correctional system, what is known as a penal process is known. The correctional process itself is interpreted as a process since a prisoner enters the correctional facility until it is released, which actually returns to the community. Keyword : prison; guidance and coaching; penal process, returns to the community.